Dashboard Security Awareness: Innovation for Enhancing Civil Servants' Cybersecurity Awareness in the Digital Era - Nur Izzuddin; Andrie Yuswanto (Badan Pengembangan Sumber Daya Manusia Provinsi DKI Jakarta, 2025)
Dashboard Security Awareness (Sec-Aw) is an integrated digital platform innovation developed to enhance cybersecurity awareness among Civil Servants (ASN) in West Jakarta. The background of this research stems from the high incidence of cybersecurity attacks in Indonesia, reaching over 330 million incidents in 2024, with 60% attributed to human negligence factors. This study aims to develop an effective cybersecurity awareness platform featuring self-assessment based on the National Cyber and Crypto Agency (BSSN) framework, interactive educational media, basic security tools, and personalized recommendations. The methodology employs Research and Development (R&D) with a mixed-method approach, Fishbone analysis for root cause identification, USG (Urgency, Seriousness, Growth) analysis for problem prioritization, self-assessment instruments adapting the Knowledge-Skill-Practice (K-S-P) framework and Multiple Criteria Decision Analysis (MCDA) approach, along with phased implementation through preparation, development, implementation, and evaluation-dissemination stages. Measurements were conducted in two waves: the initial assessment in March 2025 involving 77 ICT administrators from West Jakarta Government Work Units yielded a score of 2.48 (Poor category), while the follow-up assessment in June 2025 involving 419 employees of the West Jakarta Municipal Government demonstrated improvement to 2.97 (Good category), reflecting a 19.8% increase. Nevertheless, two areas require particular attention: Technical Incident Reporting (1.93) and Social Law/Regulation aspects (1.38). The issuance of West Jakarta Mayor's Circular regarding SPBE Security Implementation establishes Dashboard Sec-Aw as an official instrument for capacity building and self-assessment, strengthening SPBE governance and expanding coverage from the mayor's office to all work units. This platform supports the strengthening of Indonesia’s digital resilience by enhancing cybersecurity literacy and culture among government officials.